Stabilization Of Heavy Metals And Chlorine Removal In Municipal Solid Waste Incineration Bottom Ash By Carbonation Process - Gi-Chun Han (The Minerals, Metals and Materials Society, 2006)
This study focused on stabilization of heavy metals and removal of chlorine in MSWI bottom ash by artificial carbonation with washing. Artificial carbonation was carried out by applying CO2(g) injection in washing for fractions above and below 4mesh for reuse as construction materials like aggregate, As a result, carbonation with washing could satisfy Korean environmental regulation and remove chlorine in bottom ash more effectively by resolving residual friedel?s salt(3CaOAl2O3CaCl210H2O).